2009
DOI: 10.1155/2010/323410
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous RP HPLC Determination of Aceclofenac, Paracetamol and Tizanidine in Pharmaceutical Preparations

Abstract: A simple, fast and precise reverse phase high performance liquid chromatographic method is developed for the simultaneous determination of aceclofenac, paracetamol and tizanidine. Chromatographic separation of the three drugs were performed on a hypersil C18column (250 mm x 4.6 mm, 5 µm) as stationary phase with a mobile phase comprising of mix phosphate buffer pH 7.0: acetonitrile (40:60 v/v), at a flow rate of 0.7 mL min-1and UV detection at 230 nm. The proposed method was validated for linearity, accuracy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The low recovery of colchicine may be affected by the presence of the other constituents in the tablet sample. The t-test statistics reveals that for recovery results in this study for ampicillin and paracetamol are in a good agreement with the work of Barot et al 33 and Avidya et al 34 who used HPLC technique for ampicillin and paracetamol respectively.…”
Section: Recovery Testsupporting
confidence: 90%
“…The low recovery of colchicine may be affected by the presence of the other constituents in the tablet sample. The t-test statistics reveals that for recovery results in this study for ampicillin and paracetamol are in a good agreement with the work of Barot et al 33 and Avidya et al 34 who used HPLC technique for ampicillin and paracetamol respectively.…”
Section: Recovery Testsupporting
confidence: 90%
“…Methanol and water (70:30 v/v) had been used in RP-HPLC method for aceclofenac and paracetamol assay in 2 to 50 µg/mL concentration range for Aceclofenac (Godse et al, 2009). This technique has also been applied for assay calculation of aceclofenac, paracetamol and tizanidine with mobile phase as phosphate buffer pH 7.0: acetonitrile (40:60 v/v) at 0.7 mL/min flow rateand UV detection at 230 nm (Vaidya et al, 2010). In another study, acetonitrile: water: 0.025 M buffer of potassium dihydrogen orthophosphate (70:10:20% v/v/v) having pH 3.0 stabilized by orthophosphoric acid was used for assay of aceclofenac and thiocolchicoside using spectrophotometry and liquid chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…United States Pharmacopeia (USP) have analytical methodologies involving TZ, using high performance liquid chromatography (LC) for related compounds determination (USP 39, 2016). Studies using LC have been reported with tizanidine alone or in association with other drugs, but there isn`t one using association with charged aerosol detector (CAD) (2,(5)(6)(7)(8). CAD detector is a new type of detector introduced for LC applications.…”
Section: Introductionmentioning
confidence: 99%